2013
DOI: 10.1017/s1368980013002218
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, sedentary behaviours and dietary habits among Kuwaiti adolescents: gender differences

Abstract: Objective: The present study was designed to assess physical activity, sedentary behaviours and dietary habits among adolescents in Kuwait and to compare the differences between genders. Design: A cross-sectional study was conducted among secondary-school children who participated in the Arab Teens Lifestyle Study (ATLS), a multi-centre collaborative project. Setting: Secondary schools in Kuwait. Subjects: Adolescents (463 boys and 443 girls), aged 14-19 years. Results: Nearly half (44?6 %) of the boys and thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
59
5
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(82 citation statements)
references
References 32 publications
9
59
5
1
Order By: Relevance
“…Other studies have also shown females to be more sedentary [6,28,29,35,36] but Iranian females were less sedentary than their male counterparts [9]. Gender was not associated with sitting time in a study conducted among Polish students [37], these differences can be justified on grounds of social and cultural differences.…”
Section: Discussionmentioning
confidence: 95%
“…Other studies have also shown females to be more sedentary [6,28,29,35,36] but Iranian females were less sedentary than their male counterparts [9]. Gender was not associated with sitting time in a study conducted among Polish students [37], these differences can be justified on grounds of social and cultural differences.…”
Section: Discussionmentioning
confidence: 95%
“…According to problems in the field there is a need to adopt ways to increase physical activity in girls (9). In a variety of studies the researchers emphasized on the physical activity intervention in females and adolescents (11, 12). Physical activity education interventions in schools have the potential to reach a majority of adolescents (13).…”
Section: Introductionmentioning
confidence: 99%
“…Similar observation was also found in a recent study conducted in Kuwait. 5 Furthermore in our study, total prevalence of overweight and obesity among all children who were using vehicle as mode of transportation (Table 4). 77.5 % which was similar to a study conducted in elementary schools of Mexico City.…”
Section: Discussionmentioning
confidence: 53%